Influence Of Application of Accounting Information System and Human Resources Competency the Quality of The Financial Statements of The BOS Fund - Siti Nurma Sari; Sulaeman Sulaeman; Elan Eriswanto (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
The Influence of the Implementation of Accounting Information Systems and Human Resources Competence on the Quality of the Financial Statements of BOS Funds. The purpose of this study was to determine the effect of the application of accounting information systems and human resource competence on the quality of the financial statements of BOS funds partially and simultaneously. The method used in this study is a quantitative method using parametric statistics. Data collection techniques are through interviews, distributing questionnaires, documentation, and literature. The population and sample in this study were 33 in MIS in Surade sub-district, and the Ministry of Religion in Sukabumi Regency. The data analysis technique used validity test, reliability test, classical assumption test, and hypothesis testing. The results of the study using SPSS 25, it can be concluded that the application of accounting information systems and human resource competencies has a positive and significant effect on the quality of the financial statements of BOS funds. The significance value obtained through the t-test and f test are 0.00 < 0.05, which means that H0 is rejected and H3 is accepted.